A community-based randomized controlled trial providing weekly iron-folic acid supplementation increased serum- ferritin, -folate and hemoglobin concentration of adolescent girls in southern Ethiopia - Handiso, Yoseph Halala (Sci Rep, 2021)
Adequate micronutrient status during adolescence can break the inter-generational cycle of malnutrition. This study evaluated the effect of community-based weekly iron-folic acid supplementation (WIFAS) on serum ferritin (SF), serum folate (SFol) and hemoglobin concentration (Hb) among adolescent girls. A community-based, individually randomized-controlled trial (RCT) was conducted in four villages of Wolaita and Hadiya zones. Adolescent girls (n = 226) aged 10–19 years were recruited and randomly assigned (n = 113/group) into: (i) WIFAS and (ii) control (no intervention) groups. Anthropometry, Hb concentration, and serum ferritin (SF), SFol, and C-reactive protein (CRP) was analyzed at baseline and endline. Baseline Hb, SF, SFol and CRP concentrations were similar in both groups (P > 0.05). About 47–49% of adolescents had marginal iron store (< 50 µg/l). Hb, SF, and SFol concentrations increased in the intervention group, but not in the control group (P < 0.05). Marginal iron store decreased from 49 to 12% after 3-months of WIFAS; whereas, the proportion of adolescents with elevated SF (> 15 µg/l) was slightly higher in the WIFAS than in the control group (P = 0.06). After adjusting for confounding factors in the multiple linear regression model, a three-months WIFAS intervention was associated with an improvement of 4.10 ng/ml in serum folate, 39.1 μg/l in serum ferritin, and 1.2 g/dl in hemoglobin concentration relative to the control group (P < 0.001). WIFAS intervention for three-months was effective in reducing iron and folate deficiency in adolescent girls. Future studies should evaluate the long-term impact of intermittent WIFAS.